Comparative Morphometry of the Skull of Hair Goat (Capra aegagrus hircus) using Different Measurement Methods: a Methodological Study - Kanmaz, Yesım Aslan; Atlı, Muhammed Zahid (My University, 2025)
Morphometry is the branch of science that deals with the problems that arise in terms of shape by using various methods. In this sense, different measurement methods are used. The traditional morphometry technique that has been going on for years is based on measurements with digital callipers. With technological developments, three-dimensional (3D) modelling from images obtained with imaging systems has increased, which gives morphometric results closer to reality in irregular structures. For 3D modelling, images obtained from imaging systems such as CT and MRI are modelled using different software and morphometric data are obtained. In addition to these imaging systems, 3D models can also be created from images obtained with a tool called photogrammetry. The aim of this study is to determine the craniometric data of Hair goats by using different measurement methods. For this purpose, a total of 14 Hair goat skulls, 7 female and 7 male, were used. From each skull, 38 parameters were measured with the specified measurement methods (digital calliper, modelling with photogrammetry and modelling with 3D-slicer programme). Seven index calculations and statistical analyses were performed. As a result of the analyses, a statistical difference was determined between the techniques in 16 parameters in male goats, while the difference was observed in 13 parameters in female goats. In addition, facial index 1 and orbital index values in male goats differed between the methods, while differences were observed in facial index 1, basal index and palatal index values in female goats (p<0.05). As a result of the study, it was thought that the use of images and 3D models obtained from bones scanned with different methods should be a priority in osteometric measurements, especially since the results of measurements made in a digital environment provide closer results to reality. Since the skull bones used in the study consist of irregular bones, it is thought that differences may be observed, but statistical differences between the methods should not be ignored.
Keywords: Hair goat; methodology; Craniometry; photogrammetry; 3D modelling